Expression and functional relevance of UGT1A4 in a cohort of human drug‐resistant epileptic brains. Issue 9 (19th July 2013) - Ghosh, Chaitali; Hossain, Mohammed; Puvenna, Vikram; Martinez‐Gonzalez, Jorge; Alexopolous, Andreas; Janigro, Damir; Marchi, Nicola
Summary Purpose Brain drug bioavailability is regulated by the blood–brain barrier (BBB). It was recently suggested that cytochrome P450 (CYP) enzymes could act in concert with multidrug transporter proteins to regulate drug penetration and distribution into the diseased brain. The possibility that phase II metabolic enzymes could be expressed in the epileptic brain has been not evaluated. Phase II enzymes are involved in the metabolism of common antiepileptic drugs (AEDs). Methods Phase II enzyme UGT1A4 brain expression was evaluated in temporal lobe resections from patients with epilepsy. UGT1A4 expression was determined by western blot and immunocytochemistry in primary cultures of human drug‐resistant brain endothelial human brain epileptic endothelial cells (EPI‐EC)s and commercially available control cells human brain microvascular endothelial cells (HBMECs). Lack of DNA condensation measured by 4′, 6‐diamidino‐2‐phenylindole (DAPI) was used as a surrogate marker of cell viability and was correlated to UGT1A4 expression high performance liquid chromatography ultraviolet detection (HPLC‐UV) was used to quantify lamotrigine metabolism by EPI‐EC and HBMEC. The appearance of the specific lamotrigine metabolite, 2‐n glucuronide (MET‐1), was also evaluated. Lamotrigine and MET‐1 levels were measured in selected surgical brain and matched blood samples. Key Findings UGT1A4 expression was observed in BBB endothelial cells and neurons. Our quantification study revealed variable levels of UGT1A4 expression across the brain specimens analyzed. Neurons devoid of UGT1A4 expression displayed nuclear DAPI condensation, a sign of cellular distress. UGT1A4 overexpression in EPI‐EC, as compared to HBMEC, was reflected by a proportional increase in lamotrigine metabolism. The lamotrigine metabolite, MET‐1, was formed in vitro by EPI‐EC and, to a lesser extent, by HBMEC. HPLC‐UV measurements of brain and blood samples obtained from patients receiving lamotrigine prior to surgery revealed the presence of lamotrigine and its metabolites in the brain. Significance These initial results suggest the presence of a phase II enzyme in the epileptic brain. Further studies are required to fully describe the pattern of brain UGT1A4 expression in relation to clinical variables and drug resistance.